Penerapan Teknik Penyuntingan Kontinuitas dalam Video Dokumenter “Batas Tanpa Batas” - Iwan Koswara; Jimi Narotama Mahameruaji; Hardifa Reinka Khairani (Comit: Communication, Information and Technology Journal, 2024)
Inclusive and equitable education for children with special needs (ABK) in Indonesia still faces various significant challenges. This writing analyzes the application of continuity editing techniques in the documentary video "Batas Tanpa Batas" which tells the story of Djulaiha Sukmana's struggle in establishing Yayasan Biruku, an institution that provides quality education for ABK who are often marginalized from the conventional education system. The role of the editor in this documentary is crucial, not only as a visual processor but also as an influential agent in shaping public perception and sparking discussions about the importance of inclusive education. The writer as an editor uses continuity editing techniques such as L-Cut, Cutaway, and Color Grading to create a cohesive and emotional narrative. The editing process also includes offline and online stages, which aim to optimize visuals and audio to strengthen the message conveyed. This documentary shows that the editor has a strategic role in managing the story flow and ensuring effective transitions between scenes, so that the message about the importance of inclusive education can be well conveyed to the audience. The purpose of this writing is to enhance understanding of the important role of editors in supporting advocacy for inclusive education for ABK through documentary media. Additionally, this effort aims to identify and evaluate effective methods in content presentation that can influence and change society's views on inclusive education.